2015
DOI: 10.1016/j.molp.2015.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Plant Ethylene Responses by Controlling Essential Protein–Protein Interactions in the Ethylene Pathway

Abstract: The gaseous plant hormone ethylene regulates many processes of high agronomic relevance throughout the life span of plants. A central element in ethylene signaling is the endoplasmic reticulum (ER)-localized membrane protein ethylene insensitive2 (EIN2). Recent studies indicate that in response to ethylene, the extra-membranous C-terminal end of EIN2 is proteolytically processed and translocated from the ER to the nucleus. Here, we report that the conserved nuclear localization signal (NLS) mediating nuclear i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 30 publications
5
39
0
Order By: Relevance
“…The ethylene receptors also interact with EIN2 (Bisson et al, 2009;Bisson andGroth, 2010, 2015), a central positive regulator in the ethylene-signaling pathway (Alonso et al, 1999) that acts downstream of CTR1 (Roman et al, 1995;Ju et al, 2012). Arabidopsis ein2 mutants are completely insensitive to ethylene (Alonso et al, 1999), and mutants of EIN2 orthologs in rice , Medicago truncatula (Penmetsa et al, 2008), and Lotus japonicus (Miyata et al, 2013) also display ethylene-insensitive phenotypes.…”
Section: Dynamic Associations Of the Ethylene Receptors With The Downmentioning
confidence: 99%
See 1 more Smart Citation
“…The ethylene receptors also interact with EIN2 (Bisson et al, 2009;Bisson andGroth, 2010, 2015), a central positive regulator in the ethylene-signaling pathway (Alonso et al, 1999) that acts downstream of CTR1 (Roman et al, 1995;Ju et al, 2012). Arabidopsis ein2 mutants are completely insensitive to ethylene (Alonso et al, 1999), and mutants of EIN2 orthologs in rice , Medicago truncatula (Penmetsa et al, 2008), and Lotus japonicus (Miyata et al, 2013) also display ethylene-insensitive phenotypes.…”
Section: Dynamic Associations Of the Ethylene Receptors With The Downmentioning
confidence: 99%
“…In Arabidopsis, it was shown that the HKlike domain of the ethylene receptors interacts with the C-terminal domain of EIN2 (Bisson et al, 2009;Bisson and Groth, 2010). Blocking or mimicking His phosphorylation on ETR1 resulted in reduced or increased affinity with EIN2, respectively (Bisson and Groth, 2010), and a nuclear localization signal in the EIN2 C-terminal domain is important for this interaction (Bisson and Groth, 2015). The direct interaction of EIN2 with the receptors could be consistent with an alternative pathway of ethylene receptor signaling that bypasses CTR1; such a pathway has been implicated by the finding that overexpression of the ETR1 N-terminal domain partially suppresses the constitutive ethylene response phenotype of the Arabidopsis ctr1-1 mutant (Qiu et al, 2012).…”
Section: Dynamic Associations Of the Ethylene Receptors With The Downmentioning
confidence: 99%
“…This might be due to the different target points of 1‐MCP and NOP‐1 in the ethylene signalling pathway. Whereas 1‐MCP blocks ETR, NOP‐1 causes downstream impairment through an ETR–EIN2 interaction . However, NOP‐1 appears not to affect autocatalytic ethylene production or respiration and this might be one reason to explain its weak influence on the ripening of ‘Golden Delicious’ apples (Figs (A), and ) …”
Section: Discussionmentioning
confidence: 99%
“…The in vitro studies provide biochemical mechanisms for ethylene signaling that is 1 coupled with inhibited ETR1 autophosphorylation and increased ETR1-EIN2 interaction 2 (Bisson and Groth, 2010;Bisson and Groth, 2015). However, the role of the ethylene 3 receptors in ethylene signaling suppression has been well defined genetically, and the 4 kinase-defective ETR1 proteins repressed the ethylene response more effectively than the 5 wild-type ETR1 in Arabidopsis; the ETR1 autokinase activity may facilitate and not 6 inhibit ethylene responses.…”
mentioning
confidence: 99%
“…Moreover, the strong 24 interaction of EIN2 with the kinase-defective ETR1 could facilitate the EIN2 cleavage 25 but hinder the release of the EIN2 C-terminus for ethylene signaling and thus weaken the 26 ethylene responsiveness, as evidenced by the EIN2-CEND-GFP partly localization at the 27 ER (Bisson and Groth, 2010;Bisson and Groth, 2015;Wen et al, 2012). The ER-retained …”
mentioning
confidence: 99%